Integrated Application of Selected Elements of Sustainability, Circular Economy, Bioeconomy, and Environmental Management System in Guesthouses - Petr Scholz; Pavla Vrabcová; Ivica Linderová; Hana Kotoučková (BioResources, 2023)
Efforts to minimize negative effects on the environment are manifested in the hospitality sector in the form of integrated application of elements of sustainable business, circular economy, bioeconomy, and environmental management. Those who run accommodation facilities are becoming environmentally aware and feel that they should be more involved in sustainable practices and thus contribute to improving the environment both locally and nationally. The main goal of this study is to identify and evaluate the application of selected elements and measures of sustainable business, circular economy, bioeconomy, and environmental management in guesthouses of the Czech Republic. A questionnaire survey (n1 = 343) was carried out together with a qualitative focus group method (n2 = 5); the data evaluation was carried out using advanced statistical methods (Tukey HSD test, Kruskal-Wallis test, correspondence analysis). The results showed that a higher classification in the guesthouse is associated with an increasing trend in the number of environmentally friendly operating methods used. Measures related to waste sorting containers (74%) and energy-saving and LED light bulbs (68%) showed the highest values. The results are useful for the practice of national professional associations that support the careful handling of resources and thereby influence the entire hospitality sector.